Análisis De Calidad De Las Semillas De Especies Arbustivas De Los Bosques Siempre Verde Pie Montano, Montano Y Montano Bajo De La Zona Noroccidental De La Provincia De Cotopaxi. - Velasque Chanaluisa, José Leonardo (2018)
The analysis of the quality of the shrubby seeds was carried out at three climatic floors that includes, from the 600 to the 3100 m.s.n.m, corresponding to the evergreen montane, montane and low montane forest of the northwestern zone, in the Esperanza sector, Tingo Parish, Pujilí Canton, Cotopaxi Province, in order to morphologically characterize the seeds of the shrub species that currently exist in the place. For identification and morphological characterization different descriptors were used, mimes that helped to determine in the first instance the type of fruit, consequently the shape of the seed, the thickness, width and length, the color of the seed and the test, position of the radicle, texture of the testa and finally the shape of the embryo, which each one presents. It wos to identify 4 individuals corresponding to 4 species of 4 shrub families, where we determined that the highest degree of germination presents the species Colca Colorada with 70% and Sacha coffee with 17%. The percentage of greater humidity that presents Colca Colorada is of 28% in relation to Sacha Café that presented 35%, in relation to the White Musuelo that reflects the 17% of humidity respectively. Of the species that were evaluated all have round shape in the seeds, the color of the seed have certain similarity located in the Pantone-Golden Palm code 17-0839 TPX, the thickness of these is between the ranges of 15,705 mm to 3.77mm, the width of their average ranges are between 13.24 to 3.15mm, the length is the ranges of 28.52mm to 4.36mm. In this virtue, it can be stated that the morphological characteristics of the seeds are almost homogeneous in their phenotypic characteristics but show marked differences in their internal characteristics due to the different environmental conditions that prevail in the sector.